Videoconferencing vs. Face-To-Face: A Comparison of Results from Two Articulation Testing Conditions - Nickel, Natasha; Flottemesch, Christen; Morrical, Deirdre; Axani, Carly (2011)
The use of videoconferencing to provide speech-language services has been promoted by such agencies as Alberta Health Services. It allows previously un-serviced, rural areas to access direct speech services from a speech-language pathologist (SLP), while also reducing the costs associated with traveling therapists. However, little research has been conducted on the validity of articulation assessments in child populations via videoconferencing. The purpose of this study was to determine whether or not the same results would be obtained from an articulation test administered under two conditions: face-to-face (FTF) and videoconferencing (VC). A computer-based articulation screening tool was administered to 33 kindergarten children in Lac La Biche, Alberta. Each participant was tested in both conditions, with the order of administration counterbalanced and with approximately four weeks between each administration. Results were compared across the two conditions using paired t-tests. Specific measures included the number of target sounds in error, the number of target sounds produced correctly (overall and by word position and sound class – fricatives, stops, etc.), prompt use and test administration time. Results showed that there was no significant difference between scores obtained in the VC and FTF condition. However, in the VC condition, children required more prompting and test administration time was longer. Certain sound classes (i.e. nasal and liquids) scored better in the VC condition. Overall, it was found that videoconferencing is a valid avenue to screen kindergarten children for articulation errors. However, small perceptual differences in articulation may be more difficult to identify.